Integrated Vaccination And Biosecurity Approaches In Military Operational Readiness - Lila Irawati Tjahjo Widuri (UNIVERSITAS PAKUAN, 2026)
Military operational readiness is increasingly challenged by infectious diseases and emerging biological threats that may disrupt mission continuity, particularly in geographically diverse settings such as Indonesia. As an archipelagic country with heterogeneous endemic disease patterns and frequent military deployments to remote and maritime areas, strengthening force health protection represents a critical public health priority. This systematic literature review aimed to examine the strategic role of vaccination and biosecurity in enhancing military operational readiness and to identify implications for national defense health systems. A systematic literature review design was conducted following PRISMA guidelines. Electronic searches were performed in PubMed, Scopus, Semantic Scholar, CrossRef, and Google Scholar for peer-reviewed studies published between January 2020 and December 2024. Studies addressing vaccination programs, biosecurity measures, and their impact on military readiness were included, and 25 eligible articles were analyzed using qualitative thematic synthesis. Four principal domains were identified: Force Health Protection, Biodefense, Operational Logistics, and Civil–Military Cooperation. Preventive vaccination and pre-deployment biosecurity training were the most emphasized strategies and were associated with reduced disease transmission and improved operational continuity. However, logistical constraints, physiological stressors, and vaccine hesitancy emerged as key implementation barriers. These findings highlight the need for an integrated biodefense framework tailored to Indonesia’s defense health system to strengthen preparedness, resilience, and sustainable operational readiness.